Les tribus dispersées - Ben-Zvi, Itzhak; Poliakov, Léon; Cassin, René (Paris : Les Editions de Minuit, 1959)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: joodse gemeenschap; maranisme; Midden-Oosten.; Kaukasus; Iran; Afghanistan